Hybrid structures: innovative governance, judicial and sociological approaches - Aliu, Armando; Parlak, Bekir; Aliu, Dorian (Quality & quantity, 2015)
The aim of this study is to examine the new trends in the hybridity research area and clarify the convergence of interests among state actors, private actors and civil society actors. Hybridity is perceived as a multidimensional phenomenon and new paradigm in various industries. The effective collaboration among public sector-private sector-civil society can be attained likelihood with taking into account regional governance and multilevel governance. Hybridity at global governance level covers decentration (supra: centralization and infra: decentralization; or politically/socioeconomically: quasi-decentralization and culturally: denationalization) which includes the nexus of voice (democratic participation) and entitlement (legal/social rights and duties). In this framework, this study explores state and non-state interactions at multiple levels and attempts to clarify how hybridization provides triple win solution for state actors, private actors and civil society actors related issues in realm of theory/praxis dichotomy. Through enhancing legitimacy and effectiveness of the activities and efforts of non-state actors in the framework of (quasi)indirect centralization process, states ensure reciprocal understanding. In this study, constructivism was followed as paradigmatic research method.
Published: 31 January 2014
Gesehen am 22.07.2020